Coarctation of the Aorta in the Adult - Kaemmerer, Harald; Hager, Alfred; Hess, John (SA Heart Journal, 2017)
Coarctation of the aorta is a complex systemic cardiovascular disease. The most prominent feature is the stenosis at the aortic isthmus that can be removed surgically or by catheter intervention. However, there are often concomitant cardiovascular problems like a bicuspid aortic valve, vascular wall abnormalities, arterial hypertension and vascular aneurysms. Therefore, regular life-long medical follow-up is necessary including modern imaging techniques, even after successful primary treatment.